50 simple things kids can do to save the earth - Montez, Michele; Earth Works Group (U.S.) (Kansas City, MO : Andrews and McMeel, 1990)
Explains how specific things in a child's environment are connected to the rest of the world, how using them affects the planet, and how th e individual can develop habits and projects that are environmentally s ound.
Keywords: Environmental protection -- Citizen participation -- Juvenile litera ture; Environmental protection